2019
DOI: 10.31744/einstein_journal/2019ao4419
|View full text |Cite
|
Sign up to set email alerts
|

Body composition, strength static and isokinetic, and bone health: comparative study between active adults and amateur soccer players

Abstract: Objective: To compare tissue composition, total and regional bone mineral content and bone mineral density, static hand grip and knee joint isokinetic strength between amateur soccer players and Control Group. Methods: Cross-sectional study. Air displacement plethysmography was used to estimate body volume and, in turn, density. Body composition, bone mineral content and bone mineral density were assessed for the whole body and at standardized regions using dual energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The mean score of the EG was almost 18% higher (approximately 9 cm) than that of the NEG with the lowest score (NEG-B). A previous study which aimed to compare the handgrip performance of a group of amateur soccer players and a group of healthy adults concluded that soccer players attained larger mean values in handgrip than the control group (+5.6 kg, p ≤ 0.01) [30]. Indeed, these results would be expected due to the systematic training that amateur soccer players are submitted to.…”
Section: Discussionmentioning
confidence: 87%
“…The mean score of the EG was almost 18% higher (approximately 9 cm) than that of the NEG with the lowest score (NEG-B). A previous study which aimed to compare the handgrip performance of a group of amateur soccer players and a group of healthy adults concluded that soccer players attained larger mean values in handgrip than the control group (+5.6 kg, p ≤ 0.01) [30]. Indeed, these results would be expected due to the systematic training that amateur soccer players are submitted to.…”
Section: Discussionmentioning
confidence: 87%
“…It is therefore probable that rink-hockey players may have higher grip strength, given these neuromuscular adaptations from training [ 17 ]. In fact, our results reveal that elite hockey players have noticeable higher values than active adults and amateur soccer players [ 51 ]. However, when compared with elite ice hockey athletes, the values of elite rink hockey grip strength are lower and differences within both hands are greatly evident [ 18 ].…”
Section: Discussionmentioning
confidence: 99%